Use of oral fluids for efficient monitoring of influenza viruses in swine herds in Colombia - Ciuoderis, Karl A; Perez, Laura S; Cardona, Andrés; Hernandez-Ortíz, Juan Pablo; Osorio, Jorge E (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Influenza A virus (IAV) surveillance in swine is critical not only due to the direct impact of the disease in the pork industry but also because IAV are prone to interspecies transmission (from human to pigs and vice versa); therefore, its monitoring is fundamental from a public and animal health perspective. Several diagnostic techniques have been used to detect IAV infection from nasal samples in swine, while samples of oral fluids (OF) are in use as novel alternatives for pathogen detection. The OF allow for efficient and feasible low-cost disease detection at the herd level, with low risk of stress for the animals. Objective: To describe a surveillance strategy of IAV at the herd level during respiratory disease outbreaks in swine farms at tropical settings using porcine oral fluids. Methods: An active surveillance strategy was conducted in several farms with past records of respiratory disease. The IAV detection was conducted in five purposively selected swine farms from years 2014 to 2017. We investigated a total of 18 respiratory outbreaks of the disease. Swine OF were collected for IAV testing. An OF sample is described as a pen-based specimen collected from a group of >20 pigs per pen and/or per barn (stall-housed individually with close contact among them). The IAV infection was investigated in OF by rRT-PCR testing and confirmed by viral isolation in cell culture. Results: We found 107 (7.4%) positives to IAV by rRT-PCR from a total of 1,444 OF samples tested. Additionally, 9 IAV isolates were all further identified as H1 subtype. Conclusions: Our results demonstrate that OF can be easily implemented as a novel, user-friendly, welfare-friendly, accurate and cost-effective sampling method for active surveillance and monitoring of IAV infections in swine farms in tropical settings.